LESTARIKAN WARISAN LELULUR DENGAN PENGELOLAAN SITUS MAKAM KERAMAT MBAH SETYO SETUHU - Rahmawati Rahmawati; Fredella Adyuta Hartoyo; Septi Dwi Nenggar Sari (Universitas Islam Malang, 2022)
Patokpicis is one of the villages located in Wajak District, Malang Regency. In the village there is one historical site in the form of a tomb. The tomb is the tomb of Mbah Setyo Setuhu. This tomb is located in the Keramat Hamlet, Patokpicis Village. The tomb has its own history, especially for the residents of Ngadas Poncokusumo Village. This historical site has a story about the origin of hanacaraka. This tomb is often visited by residents and pilgrims, especially on certain nights, but is poorly maintained because it is far from settlements. The service implementation team has a program for preserving historical sites at the tomb with methods of socialization, education, and mentoring. The objectives of this program are: 1) Keeping the building looking a little tidier; 2) Maintain the environment so that the pilgrims are comfortable when visiting; 3) Introducing this historical site to the wider community. The result of this preservation program is that the tomb is cleaner and neater.